108 Evaluation of Graded Levels of Grain Distillers Dried Yeast (GDDY) on Apparent Nutrient Digestibility and Stool Quality in Healthy Adult Dogs. (8th October 2021) - Kilburn, Logan; Jolly-Breithaupt, Melissa L; Balk, Derek; Aldrich, Charles G
Abstract: Yeast and distillers' grains from ethanol products have been included in pet food for many years. However, their combination has not been evaluated in pet food. Grain distillers dried yeast (GDDY) is a combination of fermented grains which is rich in yeast. The objectives of this study were to determine the effects of increasing levels of GDDY on apparent total tract digestibility (ATTD) and stool quality in adult dogs. Four extruded diets were fed to twelve adult Beagle dogs in a replicated 4 x 4 Latin Square design. The control diet contained 15% soybean meal (15S) and GDDY was exchanged for soybean meal at either 5%, 10%, or 15% (5G, 10G, 15G). Dogs were fed each dietary treatment for 9-d adaption followed by 5-d total fecal collection. Feces were scored on a 1–5 scale, with 1 representing liquid diarrhea. Titanium dioxide was added to all diets (0.4%) as a marker to estimate digestibility. Data were analyzed using a mixed model in SAS (version 9.4, SAS Institute, Inc., Cary, NC) with treatment as a fixed effect and dog and period as random effects. No differences (P > 0.05) were observed in wet fecal output or fecal pH (average; 112.74g/d and 5.77). Fecal DM and defecations per day were greater (P < 0.05) at elevated levels of GDDY. Stool scores were higher (P < 0.05) when dogs consumed diets containing GDDY versus 15S (average; 3.85 vs 3.67). Organic matter ATTD was the greatest (P < 0.05) for dogs fed 15S compared to GDDY treatments (average; 87.64% vs 86.67%). Dogs fed 10G had the lowest (P < 0.05) ATTD for crude protein compared to all others (average; 87.92% vs 88.78%). These results suggest that levels of GDDY between 5 and 15% are comparable to soybean meal when fed to adult dogs.